The cleptoparasitic bee genus Odyneropsis in México (Hymenoptera, Apidae, Epeolini) - Roig-Alsina, Arturo (Journal of Melittology, 2024)
A new species of cleptoparasitic bees, Odyneropsis chamelae Roig-Alsina, new species, is described from the state of Jalisco, México. Odyneropsis apache Griswold and Parker, described from southwestern USA, is reported for the first time in México. Odyneropsis apicalis Ducke was the only species previously known to occur in México and a lectotype is designated. Notes on the variability of O. apicalis in color and morphology, a key to the Mexican species, and distributional data are presented.